2011
DOI: 10.1007/s12011-011-9097-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium on Connexin Expression, Angiogenesis, and Antioxidant Status in Diabetic Wound Healing

Abstract: This study was done to analyze the effect of selenium on antioxidant status and expression of different connexins in diabetic wound healing. The levels of vascular endothelial growth factor, superoxide dismutase, lipid peroxide, and connexins were analyzed in wound tissues taken from diabetic and non-diabetic mice before and after sodium selenite administration. The mRNA transcript levels of Cx 26, 30.3, 31, 31.1, and 43 were significantly elevated in diabetic wounds as compared to the non-diabetic wounds. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…Pretreatment with Se, Zn and the combination, but not Cr(pic)3 significantly increased the cardiac levels of VEGF, which implies that these elements had angiogenic effects in hypoxic conditions. While Se exhibited angiogenic effects in our study and in diabetic states (65), previous data support an anti-angiogenic effect of Se in the chemoprevention of many types of cancer (66,67) which imply that Se may act as anti-angiogenic or angiogenic depending on physiologic and metabolic conditions.…”
supporting
confidence: 70%
“…Pretreatment with Se, Zn and the combination, but not Cr(pic)3 significantly increased the cardiac levels of VEGF, which implies that these elements had angiogenic effects in hypoxic conditions. While Se exhibited angiogenic effects in our study and in diabetic states (65), previous data support an anti-angiogenic effect of Se in the chemoprevention of many types of cancer (66,67) which imply that Se may act as anti-angiogenic or angiogenic depending on physiologic and metabolic conditions.…”
supporting
confidence: 70%
“…Tumors need specialized environments to grow and thrive in. As the tumor grows, new blood vessels need to form to provide the cells with oxygen and all of the treatment options selected are able to inhibit angiogenesis, except vitamin B and selenium, both of which show mixed results [408] , [409] , [410] , [411] , [412] , [413] , [414] , [415] , [416] , [417] , [418] , [419] . Interestingly though, in regards to other factors that contribute to the tumor microenvironment, all compounds are able to provide therapeutic value [395] , [420] , [421] , [422] , [423] , [424] .…”
Section: Complementary Effects On the Enabling Characteristics Of Canmentioning
confidence: 99%
“…A transcriptomic analysis in normal rats showed that angiogenic genes were affected by selenite supplementation [64]. However, in diabetic mice, selenium (provided as selenite) has been shown to promote angiogenesis and, thereby, wound healing [65]. Both pro- and anti-apoptotic effects have been demonstrated with selenium supplementation.…”
Section: Biphasic Effects Of Selenium Statusmentioning
confidence: 99%